2018
DOI: 10.1089/cmb.2016.0093
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the LncRNA, miRNA, and mRNA Regulatory Network in Prostate Cancer with Bioinformatics Software

Abstract: Information processing tools and bioinformatics software have significantly advanced researchers' ability to process and analyze biological data. Molecular data from human and model organism genomes help researchers identify topics for study, which, in turn, improves predictive accuracy, facilitates the identification of relevant genes, and simplifies the validation of laboratory data. The objective of this study was to explore the regulatory network constituted by long noncoding RNA (lncRNA), miRNA, and mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 33 publications
2
46
0
Order By: Relevance
“…To further investigate the underlying mechanism by which miR‐188 regulates the aging‐associated metabolic phenotype, we used online tools, including TargetScan 6.2 (http://www.targetscan.org/) and miRanda (http://www.microrna.org/microrna/), to predict the potential targets of miR‐188 (He, Han, et al, ; Savita & Karunagaran, ). Among the predicted target genes, our attention was drawn to Prdm16 , because sequence analysis revealed there was a conserved miR‐188 binding site in its 3' UTR (Figure a), meanwhile PRDM16 has been reported to function as a key transcription factor that regulates the expression of thermogenic program genes in brown and beige adipocytes (Cohen et al, ; Harms et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate the underlying mechanism by which miR‐188 regulates the aging‐associated metabolic phenotype, we used online tools, including TargetScan 6.2 (http://www.targetscan.org/) and miRanda (http://www.microrna.org/microrna/), to predict the potential targets of miR‐188 (He, Han, et al, ; Savita & Karunagaran, ). Among the predicted target genes, our attention was drawn to Prdm16 , because sequence analysis revealed there was a conserved miR‐188 binding site in its 3' UTR (Figure a), meanwhile PRDM16 has been reported to function as a key transcription factor that regulates the expression of thermogenic program genes in brown and beige adipocytes (Cohen et al, ; Harms et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Mounting evidence suggested that lncRNAs may exert functions by targeting miRNAs . Bian et al confirmed that UCA1 worked as a ceRNA in colorectal cancer, regulated the expression of miR‐204‐5p and induced the resistance to 5‐FU in CRC .…”
Section: Discussionmentioning
confidence: 99%
“…The r > 0.95 and p-value < 0.05 were utilized for screening the signi cant results. Using miRanda database 25 (http://www.microrna.org), the miRNAs targeting the DE-lncRNAs and the DE-mRNAs were predicted.…”
Section: Co-expression Analysis and Prediction Of The Genes Targeted mentioning
confidence: 99%